Case studies of SARS-CoV-2 treated with favipiravir among patients in critical or severe condition. (November 2020) - Takahashi, Hidenori; Iwasaki, Yoshinobu; Watanabe, Takayasu; Ichinose, Naoki; Okada, Yasusei; Oiwa, Akito; Kobayashi, Takehiro; Moriya, Mariko; Oda, Toshimi
Highlights: Case studies of SARS-CoV-2 pneumonia focusing on the effectiveness of favipiravir. Patients were all in a deteriorating, critical, or severe condition. All patients showed a clinical and chest imaging improvement. All patients recovered without subsequent hypoxemia. Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak is rising globally. However, clinically effective antiviral treatments are not established. Favipiravir may prevent pneumonia and acute respiratory distress syndrome aggravation. We describe SARS-CoV-2-positive patients, two of whom were in a critical condition and one of whom was in a severe condition, who were administered favipiravir for their deteriorating conditions and cured.